EVALUATE THE EFFECT OF SALVIA OFFICINALIS AND CARDAMOM ON ANIMAL PRODUCTIVITY OF BROILER CHICKENS - Sawsan Abdul Faraj Mohammed; Ruya Fareed Jasim (Journal of Medical Genetics and Clinical Biology, 2024)
It is in considerable demand to produce poultry meat and eggs of superior quality at affordable costs without using growth promoters or antibiotics, so the current study aimed to evaluate the effect of Salvia officinalis and Cardamom on animal productivity of broiler chickens. This experiment was carried out at the poultry field of the Agricultural Experiment Station, College of Agriculture, Tikrit University. Ninety unsexed, one-day-old Ross 308 broiler chicks were employed. The results showed that the hemoglobin concentration, RBC counts and PCV of S. officinalis boilers and cardamom boilers indicated a significant (P≤0.05) elevated compared to the standard diet boilers. While, WBC count of S. officinalis boilers and cardamom boilers indicated non-significant (P≤0.05) elevated compared to the standard diet boilers. For antioxidant enzymes, the glutathione and catalase levels of S. officinalis boilers and cardamom boilers indicated a significant (P≤0.05) elevated compared to the standard diet boilers. Finally, total protein and albumin activities of S. officinalis boilers and cardamom boilers indicated a significant (P≤0.05) reduced compared to the standard diet boilers. It is concluded from the current study that both S. offcinalis and cardamom showed a stimulating effect on blood parameters and raising protein levels. S. offcinalis and cardamom can be considered an enhancer of the performance of broiler chickens.